Reusable glassware for routine cell culture—a sterile, sustainable and affordable alternative to single-use plastics - Trusler, Emily C.; Davies, Merlin; Spurrier, Benjamin; Gould, Samantha J. (Frontiers in Sustainability, 2024)
Cell culture is a cornerstone of in vitro biological research. Whilst glassware was once commonplace in tissue culture facilities, in recent decades laboratories have moved towards a heavy reliance on single use plastics for routine procedures. Single use plastics allow for accessible, sterile, and often affordable equipment that comes at a high environmental cost.We developed a glassware preparation and cleaning process that allowed the comparison of "traditional" plastic-heavy, and adapted "sustainable", cell culture practices, to empirically compare the sterility, viability, and proliferative capacity of cells cultured with differing techniques, by observing IL-6 production, morphology, and proliferation rate of cultured human pulmonary fibroblast cells. During which, we calculated the carbon footprint of traditional versus sustainable methods. We additionally endeavoured to provide a realistic overview of the steps required to transition to more sustainable cell culture practices and make suggestions to ease the cost, labour, and time required to uptake similar practices in other laboratories.Cells cultured using reusable glassware did not show signs of contamination or stress compared to cells grown solely with plasticware, and glassware baked at 180°C for 120 minutes was sufficiently decontaminated and depyrogenated for culturing these cells. An individual researcher adopting the same methodology could reduce their carbon footprint by 105.92 kg of Carbon dioxide equivalent (CO2e) whilst also saving money (£408.78) over a 10-year period. We predict that these benefits would be greater if more researchers were to uptake these adapted practices.We intend for this paper to reassure researchers that viable, sterile, and sustainable routine cell culture can be achieved with little upfront cost to the researcher, with the prospective benefit of greatly reducing the cost to the environment. We additionally hope that increased uptake, and thus demand of more sustainable practices, encourages suppliers, policy makers, and funding bodies to make sustainable practices more accessible to individual researchers and institutions worldwide.